The Analysis Effect of Islamicity Performance Index on the Financial Performance of Sharia Commercial Banks in Indonesia - Herman Felani; Sri Wahyuni; Bima Cinintya Pratama (Journal of Economics Research and Social Sciences, 2020)
This research aims to find empirical effect evidence of Islamicity Performance Index on the financial performance of sharia commercial banks in Indonesia. The index of Islamicity Performance Index used in this research was the profit-sharing ratio, zakat performance ratio, equitable distribution ratio, directors-employees welfare ratio, Islamic income vs non-Islamic income, Islamic investment vs non-Islamic investment. This research used a quantitative approach and used secondary data in the form of sharia commercial bank financial statements for the periode of 2010-2018. The sampling technique in this research used purposive sampling and obtained 13 samples of sharia commercial banks with 117 observational data.  The analytical method used in this research is multiple linear regression. Based on the result of this research, it can be concluded that zakat performance ratio, equitable distribution ratio, directors-employees welfare ratio, Islamic investment vs non-Islamic investment do not affect financial performance. While the profit-sharing ratio, Islamic income vs non-Islamic income have negative effects on financial performance